Solution‐Processed Fullerene‐Based Organic Schottky Junction Devices for Large‐Open‐Circuit‐Voltage Organic Solar Cells (Adv. Mater. 4/2013). (18th January 2013) - Yang, Bin; Guo, Fawen; Yuan, Yongbo; Xiao, Zhengguo; Lu, Yunzhang; Dong, Qingfeng; Huang, Jinsong
<x xml:space="preserve">Abstract</x> The Schottky‐junction structure has been broadly applied in inorganic photovoltaic devices but has not yet been successfully applied in organic photovoltaic devices. Jinsong Huang and co‐workers report on page 572 fullerene‐based Schottky‐junction devices that can output a much larger open‐circuit voltage (∼0.95 V) than most bulk heterojunction (BHJ) organic photovoltaic devices. The efficiencies of the fullerene based Schottky‐junction devices are shown to be larger than those of the state‐of‐the‐art BHJ devices under certain conditions. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>